Potential lung attack and lethality generated by EpCAM-specific CAR-T cells in immunocompetent mouse models. (1st January 2020) - Qin, Diyuan; Li, Dan; Zhang, Benxia; Chen, Yue; Liao, Xuelian; Li, Xiaoyu; Alexander, Peter B.; Wang, Yongsheng; Li, Qi-Jing
ABSTRACT: The tumoricidal efficiency of human CAR-T cells is generally evaluated using immune-deficient mouse models; however, due to their immune-incompetency and the species-specific reactivity of a target antigen, these models are problematic to imitate CAR-T-induced adverse effects in the clinic. Epithelial cell adhesion molecule (EpCAM) is a tumor-associated antigen overtly presented on the cell surface of various carcinomas, making it an attractive target for CAR-T therapy. Here, we developed an anti-mouse EpCAM CAR to evaluate its safety and efficacy in immunocompetent mouse models. As previously reported for their human equivalents, murine EpCAM CAR-T cells exhibit promising anti-tumor efficacy in vitro and in vivo. However, after CAR-T infusion, various dose-depended toxicities including body weight loss, cytokine-release syndrome (CRS), and death were observed in both tumor-bearing and tumor-free mice. Pathological examination revealed unexpected and severe pulmonary immunopathology due to basal EpCAM expression in normal lung. While our study validates EpCAM CAR-T's potent anti-tumor efficacy, it also reveals that EpCAM CAR-T cells used for the treatment of solid tumors may cause lethal toxicity and should, therefore, be evaluated in patients with caution.